Elite wheelchair rugby players` mental skills and sport engagement using hypnosis to enhance self-efficacy in sport performers - Martin, J. J.; Malone, L. A. (Journal of Clinical Sport Psychology, 2013)
Although sport psychologists have started to examine elite disability sport, studies of comprehensive mental skill use are rare. In the current study, we examined multidimensional imagery and self-talk, as well as comprehensive mental skills (i.e., coping with adversity, goal setting, concentration, peaking under pressure, being coachable, confident, and feeling free from worry). In addition to descriptive data, we also were interested in the ability of athlete`s mental skills to predict engagement (e.g., being dedicated). Fourteen elite level wheelchair rugby players from the United States participated, and results indicated that athletes employed most mental skills. We accounted for 50% of the variance in engagement with comprehensive mental skills (Beta = .72, p = .03) contributing the most to the regression equation, while imagery (Beta = -.02, p = .94) and self-talk (Beta = -.00, p = .99) were not significant. Athletes who reported using a host of mental skills (e.g., coping with adversity) also reported being engaged (e.g., dedicated, enthused, committed) to wheelchair rugby. Athletes reporting minimal mental skill use were less engaged.